Harnessing the Power of Social Network Analysis in Medical Education - EHSAN TOOFANINEJAD; MASOMEH KALNTARION; ZEINAB MOTLAGH; SEYYED KAZEM BANIHASHEM; OMID NOROOZI (Journal of Advances in Medical Education and Professionalism)
The medical education scenery is continually changing, calling for innovative ways to support learning processes and outcomes. This letter is devoted to introducing the potential of social network analysis (SNA) as an efficient educational innovation to support medical education. Through the investigation of the connections and interactions within a network, SNA brings to light complex social dynamics that can scaffold learning processes and outcomes in medical education. In this letter, we explain the role of SNA in fostering collaboration, engagement, knowledge sharing, and professionalized education among medical students and educators. We also talk about the role of node analysis (individuals) and edge analysis (relationships) to determine influential structures, knowledge brokers, and blocks in collaboration. We discuss that personalized insights gained from SNA can guide educators to provide timely and tailored interventions. In addition, SNA can reveal hidden curricula and informal networks of learning, and evaluate teamwork and communication skills efficiently. The letter also outlines how SNA can be used to deal with students’ loneliness in social learning settings and professional fatigue through the early establishment of supportive networks and peer mentoring occasions. Backed up with evidence from the relevant research, this letter accentuates the positive impact of SNA on medical education by capitalizing on the formation of interpersonal relationships and collaboration. We conclude that by gaining a deep insight into the social connection dynamics, educators can support the knowledge exchange and support the learning processes and outcomes of medical students and future health professionals.